Preschoolers’ Attitudes, School Motivation, and Executive Functions in the Context of Various Types of Kindergarten - Kvintova, Jana; Kremenkova, Lucie; Cuberek, Roman; Petrova, Jitka; Stuchlikova, Iva; Dobesova-Cakirpaloglu, Simona; Pugnerova, Michaela; Balatova, Kristyna; Lemrova, Sona; Viteckova, Miluse; Plevova, Irena (Frontiers in Psychology, 2022)
European policy has seen a number of changes and innovations in the field of early childhood preschool education over the last decade, which have been reflected in various forms in the policies of individual EU countries. Within the Czech preschool policy, certain innovations and approaches have been implemented in the field of early children education, such as the introduction of compulsory preschool education before entering primary school from 2017, emphasis on inclusive education, equal conditions in education and enabling state-supported diversity in the education concepts of kindergartens. The aim of our study was to assess the influence of various preschool education systems in the Czech Republic in the context of psychological variables reflecting selected children’s outcomes which may contribute to future school achievement. The monitored variables were the attitudes, motivations and executive functions of children in the last year of preschool education. A comparison was made between the traditional preschool education program and the so-called alternative types of preschool education, such as Montessori, Waldorf and religious schools. The total sample was divided into four subgroups, namely a group of children attending traditional kindergartens 731 (84.9%), religious (65, 7.5%), Montessori (35, 4.1%) and Waldorf (30, 3.5%) kindergartens. To determine empirical data, the following research methods were used: Attitude Questionnaire, School Performance Motivation Scale, and Behavior Rating Inventory of Executive Function (BRIEF). The results of our survey show the fact that the type of kindergarten attended has a significant effect on the child’s level of school performance motivation, attitudes towards school as well as executive functions. Significant differences were found between the different types of kindergartens attended in the monitored variables.